Hybrid Blo-Membrane Contractori For Refinery Waste Water Treatment - Mohd Zulkifli, Mohamad Noor; Iqbal, Ahmed; R. M., Yunus
The objective of this research is to separate hydrogen sulfide (H2S) gas from refinery wastewater treatment and study the influence of composition on the membrane performance for wastewater treatment. Membranes with monosodium glutamate (MSG) as an additive have been fabricated. Four dope solutions with 22% polyamide and different ratio of formic acid /MSG has prepared. The performance of membranes is evaluated based on eight parameters. There are flow rate, turbidity, Chemical oxygen demand (COD), Biochemical oxygen demand (BOD), pH, sulfide, conductivity and Total dissolve substances (TDS). The results show that membrane with 5% of MSG giving the better results. A hybrid membrane has high effectiveness in wastewater treatment. It have been reduced the turbidity, Chemical oxygen demand (COD), Biochemical oxygen demand (ROD), pH, sulfide, conductivity and Total dissolve substances (TDS) values for refinery waste water to the accepted level and achieve the requirement for standard A and B.